Análisis del efecto del esfuerzo de succión en la capacidad soportante de cimentaciones profundas - Bagnarello-Madrigal, Fiorella (Instituto Tecnológico de Costa Rica, 2010)
The mechanics of unsaturated soil is based in net pressure and matric suctions, being the last the responsible for the shear strength and deformation behaviors. The purpose of this study is to evaluate the behavior of deep foundations in unsaturated soil by analyzing the variation in the safety factor and the optimization of the designs for different saturation degrees. This study was developed using three samples from different soils, consitency limits, particle size, simple compression and triaxial tests were performed. Using the Plastic Index and the percentage of materials passing the No. 200 from the granulometric tests, and by using a model, the Soil-Water Characteristic Curve was established, which is considered as the best representation for a un unsaturated soil, and for the behavior of the matric suction at a determined humidity. The compression tests supplied values for undrained resistance at different saturation degrees. By using the α (by Tomlinson) and λ (by Vijayvergiya y Focht, 1972), methods for deep foundation design the admissible capacity, safety factor and pile dimensions were determined according to the test obtained resistance. Depending on the saturation characteristics and the physicochemical forces between particles, the least saturated sample will have greater values of undrained resistance; which is reflected in greater values of carrying capacity for the foundation. This reduces the uncertainty of the design and optimizes it.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2010.
Keywords: Suelo; Pilotes; Cohesión; Compresión; Saturación